Keeping investors onboard: A corporate social responsibility crisis response framework - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2018)
There is evidence to suggest that managers use CSR reporting as a means to manage their firms’ CSR reputations. In this study, I jointly examine CSR reputation and CSR crisis response in the context of CSR crises, and how they can influence investor judgments and decision making. In particular, in the context of CSR crises, I build on situational crisis communication theory to develop a CSR crisis response framework which managers can use to examine and understand how specific types of CSR crises can influence their firm’s CSR reputations, which can in turn influence investor judgments and decision making. Following from that, I also specify three CSR crisis response strategies that managers can employ to manage their firms’ CSR reputations